Autonomous Monitoring System of Environment Conditions - Miedzinski, B.; Rutecki, K.; Habrych, M. (Elektronika ir Elektrotechnika, 2010)
Paper presents the developed autonomous monitoring unit combined with an early warning system for the on-line control of environment. Problems of the proper selection of the sensors and strategy of data acquisition and processing to reduce the power consumption as much as possible are discussed.